Analysis Of The Impact Of Smoke-Free Area Policies On Smoking Prevalence In Indonesia - Rachman, Arief; Handayani, Dwini (UNIVED Press, 2026)
Indonesia the highest number of smokers in ASEAN, according BPS in 2023 there are 28.62% of individuals aged 15 and older who smoked tobacco in the past month. The government aims to reduce the smoking prevalence In Indonesia through the implementation of smoke-free area (SFA) policies. Studies in various countries have shown that smoking bans policies significantly reduce smoking prevalence. However, not all regional governments in Indonesia have SFA regulation. This study is to analyze the impact of SFA policies and the duration of their implementation on the prevalence of smoking in Indonesia. This research using Logit regression model and interpreted using Marginal Effects. The findings indicate that SFA policy and the duration have varying effects across different age groups. For the adult, found that SFA policy and the duration had a negative and significant impact on smoking probability. The SFA policy is essential for the government to control the health impacts of tobacco consumption. This study is expected to provide new insights and enrich references and literature on the study of smoking bans and smoking prevalence. Moreover, it can serve as a consideration for the government in its efforts to mitigate the health impacts of tobacco consumption in Indonesia.